2021
DOI: 10.12998/wjcc.v9.i21.5932
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue prevalence in men treated for prostate cancer: A systematic review and meta-analysis

Abstract: BACKGROUND The side effects of prostate cancer (PCa) treatment are very prominent, with cancer-related fatigue (CRF) being the most common. Fatigue is a distressing symptom that interferes with daily functioning and seriously affects patient quality of life during, and for many years after, treatment. However, compared with other types of cancer, such as breast cancer, little is known about the prevalence of PCa-related fatigue. AIM To determine the prevalence of CRF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…16 Its prevalence among patients receiving ADT is estimated to be 42% to 68% and is likely compounded by the receipt of EBRT. 17,18 In the current study, patients reported being willing to trade 3 mo of life expectancy to be able to avoid ADT-related fatigue entirely, underscoring its profound perceived impact on quality of life, both among patients who had accepted and declined it. Lifestyle changes, including physical exercise and dietary modification, are considered to be the best interventions to mitigate ADT-related fatigue.…”
Section: Discussionmentioning
confidence: 66%
“…16 Its prevalence among patients receiving ADT is estimated to be 42% to 68% and is likely compounded by the receipt of EBRT. 17,18 In the current study, patients reported being willing to trade 3 mo of life expectancy to be able to avoid ADT-related fatigue entirely, underscoring its profound perceived impact on quality of life, both among patients who had accepted and declined it. Lifestyle changes, including physical exercise and dietary modification, are considered to be the best interventions to mitigate ADT-related fatigue.…”
Section: Discussionmentioning
confidence: 66%
“…In particular, it has been reported that the prevalence of fatigue in patients with PC after radiotherapy and radical prostatectomy ranges from 22% to 58% and from 16% to 26%, respectively. 60 During follow-up, seven of the 20 studies included in the systematic review showed a decline in objective cognition or demonstrated a between-group difference with greater impairment in the HT group.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients considered in this synthesis had already received treatment likely to affect cognition directly and indirectly according to the aforementioned factors. In particular, it has been reported that the prevalence of fatigue in patients with PC after radiotherapy and radical prostatectomy ranges from 22% to 58% and from 16% to 26%, respectively 60 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fatigue is well documented to significantly affect the lives of prostate cancer patients and their ability to cope with everyday activities ( Supplementary material [S11,12]) [13] . In previous studies investigating the prevalence of cancer-related fatigue for prostate cancer patients, rates have varied between 13% and 82% ( Supplementary material [S13]) [13] , [14] , [15] . A more recent meta-analysis, however, suggests prevalence in the region of 40% [13] .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In previous studies investigating the prevalence of cancer-related fatigue for prostate cancer patients, rates have varied between 13% and 82% ( Supplementary material [S13]) [13] , [14] , [15] . A more recent meta-analysis, however, suggests prevalence in the region of 40% [13] . This still represents a sizeable proportion of men with prostate cancer who experience debilitating fatigue.…”
Section: Evidence Synthesismentioning
confidence: 99%